Colour Inheritance In Tiger Barb (Puntius Tetrazona) - Md.Sheriff, Shahreza (1999)
A study to identify the colour inheritance of Tiger barb (Puntius tetrazona) through Mendelian inheritance was conducted in the Biotechnology Laboratory, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia for the duration of 10 months. Three varieties of Tiger barb that is the normal, yellow and green were subjected to three experiments consisting of breeding within and between the varieties and egg and larval observation. The result of the first breeding experiment produced 11 to 153 fries after 5 weeks with 15% to 85% survival. The normal and yellow variety produced phenotypes which were the same as their parents which indicated that these varieties were true breeding. The green variety showed a segregation producing normal and green variety with a N:G ratio of 15 :1,1:1,3:1 , 1:3 and 9:7. Breeding of the normal variety produced 5 different normal variations with mating number 5 producing 84% fries with type 2 pattern. The study has succeeded in producing a new type of normal variety.